UNSUR-UNSUR INTRINSIK PADA CERPEN âMISá¹¬ARATU MABRÅªK AFANDÄªYâ DALAM ANTOLOGI CERPEN SYABÄBUN WA GÄNIYÄTUN KARYA MAá¸¤MÅªD TAIMÅªR : ANALISIS STRUKTURAL STANTON - , LULU LATIFAH ANNISA RUHYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is aimed to discover the intrinsic elements and correlation among the elements on a short story entitled âMisá¹aratu MabrÅ«k AfandÄ«yâ on short story anthology SyabÄbun wa GÄniyÄtun by Mahmud Taimur. The theory and method used in this study is Stantonâs structural method and theory. This short story will be investigated by facts of the story